How Does Bank Syariah Indonesia's Financial Performance Measure Up Using The RGEC Method's Bank Health Assessment? - Sari, Anggi Puspita (Universitas Serang Raya, 2023)
Banks are required to conduct periodic self-assessment of their health level and take effective corrective measures using an assessment of factors including risk profile, good corporate governance (GCG), earnings, and capital, abbreviated as RGEC. The RGEC method is what banks currently use to assess the health level of banks because it is a refinement of previous methods. The degree of bank health as determined by the RGEC technique is the subject of this quantitative descriptive study, which analyzes Bank Syariah Indonesia's health for the years 2019 to 2022. The study's secondary data sources are the yearly financial reports of Islamic Commercial Banks covering the years 2019 to 2022. The following findings are derived from the debate of Bank Syariah Indonesia's Islamic banking sharia for the 2019–2022 evaluation period, The non-performing financing ratio (NPF Nett in composite position 1 may be considered to be in very good health. Conversely, Bank Syariah Indonesia's FDR ratio values in composite positions 1 and 2 might be considered highly healthy. Bank Syariah Indonesia's GCG ratio in composite position 2 may be considered healthy. The Bank Syariah Indonesia's earnings evaluation, or its capacity to turn a profit, received a composite score of 3 to 1, indicating that it is both fairly healthy and extremely healthy from 2019 to 2022. Bank Syariah Indonesia's bank capital was evaluated from 2019 to 2022, and it received a composite evaluation of 1, meaning it is in excellent condition.